2012
DOI: 10.1105/tpc.112.097188
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Growth in Arabidopsis Depend on the Daytime Temperature but Are Temperature-Compensated against Cool Nights

Abstract: Diurnal cycles provide a tractable system to study the response of metabolism and growth to fluctuating temperatures. We reasoned that the response to daytime and night temperature may vary; while daytime temperature affects photosynthesis, night temperature affects use of carbon that was accumulated in the light. Three Arabidopsis thaliana accessions were grown in thermocycles under carbon-limiting conditions with different daytime or night temperatures (12 to 24°C) and analyzed for biomass, photosynthesis, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(162 citation statements)
references
References 118 publications
3
154
2
Order By: Relevance
“…However, other factors play important roles in the regulation of starch content and turnover (Pyl et al . 2012; Martins et al . 2013), so it is difficult to interpret these changes in T6P and starch content in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors play important roles in the regulation of starch content and turnover (Pyl et al . 2012; Martins et al . 2013), so it is difficult to interpret these changes in T6P and starch content in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…RP gene co-regulation was also noted when monitoring polysome-associated transcript levels. A coordinate shift of Arabidopsis RP mRNAs out of polysome complexes was observed in response to a number of environmental stresses (Kawaguchi et al, 2004;Branco-Price et al, 2005;McIntosh and Bonham-Smith, 2006;Nicolaï et al, 2006;BrancoPrice et al, 2008;Pyl et al, 2012;Tiruneh et al, 2013;. Conversely, coordinated up-regulation of the translation of a large majority of Arabidopsis RP mRNAs was recorded in two mutants of the translational apparatus (eif3h and rpl24b) (Tiruneh et al, 2013).…”
Section: Ribosome Heterogeneitymentioning
confidence: 99%
“…For ribosome biogenesis there is the additional energy outlay for rRNA synthesis. It therefore is not surprising that both ribosome biogenesis and global levels of translation are central to energy management (Piques et al, 2009;Pyl et al, 2012;Pal et al, 2013). Situations that limit ATP and GTP availability such as hypoxia, unanticipated darkness and extended nighttime limit RP mRNA translation in Arabidopsis (Branco-Price et al, 2008;Piques et al, 2009;Pal et al, 2013).…”
Section: Ribosomes and Energy For Their Synthesismentioning
confidence: 99%
“…Besides, night warming had positive effect on SLA of both species in the current study (Table 2). Pyl et al (2012) reported that lower temperature could increase leaf thickness, and therefore decrease SLA. In the current study, the air temperature (at 5 cm aboveground) and soil temperature (at 5 cm depth) within the warmed plots increased by an average of 1.95 C and 3.10 C, respectively, compared to the control plots.…”
Section: Night Warming Effect On Photosynthesis In Late Growing Seasonmentioning
confidence: 99%